Enforcement of marine environmental law against marine pollution from land-based sources in China - Pan, Xiaolin (Frontiers in Marine Science, 2025)
Serious marine pollution has posed significant challenges to both the theory and practice of China’s marine environmental law enforcement. The entry into force of the revised Marine Environment Protection Law of China provides an opportunity to examine how China enforces marine environmental law to prevent harmful consequences of land-based marine pollution and protect marine rights and interests. This article begins with a discussion of the legal authorities responsible for marine environmental law enforcement in China, based on specific indicators, and then focuses on relevant jurisdictional issues, including jurisdictional waters of China and the exercise of such jurisdiction. Additionally, the article discusses the resolution of disputes arising from enforcement actions against marine pollution from both domestic and international legal perspectives.